Knowledge, Attitude and Practice of Thai People in Prevention and Control of Rabies - พวงหัตถ์, อภิรมย์; ธีระวิทยเลิศ, รัชนี; ธนาเจริญรัศมี, นลินภัสร์ (Disease Control Journal, 2010)
This study was a KAP survey. Data were collected by interviewing heads or members of households over 15 years old about prevention and control of rabies in animals and humans. Multistage sampling identified 5,398 interviewers in 24 provinces; Pathum Thani, Ayutthaya, Sara buri, Ang Thong, Sa Kaeo, ChonBuri, Nakhon Pathom, Phetchaburi, Surin, Chaiyaphum, Nong Khai, Roi Et, Mukdahan, Sakon Nakhon, Nakhon Sawan, Phichit, Phitsanulok, Tak, Chiang Mai, Phayao, Nakhon Si Thammarat, Surat Thani, Songkhla, and Phatthalung. Interview data were analyzed, expressed in percentage and tested by Chi-square. The study showed that most households kept dogs or cats, and keeping more dogs than cats. Majority of the households kept dogs for house guarding and as pets. Dogs were kept as pets more in the central region than in other regions. Dogs were mostly left free inside or outside the houses. 11.9% of the households reported a member bitten by a dog or cat in the past one year. Most of these were bitten by dogs and 75% of the victims saw the doctor after the bite. Most of the bites were made by own dogs. For people did not see the doctor after dog bites because they thought that small bites or the bites of baby dogs had low risk of rabies. The reasons for lack of vaccination in dogs and cats included lack of vaccination services, the animals were young (under 2 months), and the animals could not be caught for vaccination. In addition, the people were found to have incorrect knowledge about rabies signs in suspected animals, types of animals that may carry rabies, treatment of rabies patients, management of rabies-risk bites, and existence of the laws that mandate vaccination of owned dogs. Only 25% of people aged 76-90 years old were bitten by animals saw the doctor for treatment. Medical treatment seeking rate was lowest in the central region. The outcome of this study suggested improvement of rabies risk communication with emphases on disease severity, dog vaccination, avoidance of dog bites and proper management of animal bites. Vaccination service for animals should be strengthened.